The faculty within the architecture of Iaşi - Costea Ramona (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2023)
The growth and dissolution of our built environment and architectures is, perhaps, a vivid representation of how memory functions, preserving most of what stands the challenge of time and “forgetting”, sometimes in a natural manner, sometimes altered by trauma and sometimes fuelled by the lack of understanding, appropriation and connection with the users’ culture and knowledge. The evermore divided world today reflects in a landscape of architecture lacking, at times, semantic coherence and connection to a broader paradigm. Of course, the visionary endeavor and experiment is mostly an unintended exercise within the design tasks of a Faculty of Architecture, serving mostly as a more or less defined urban, historic urban structure. Yet, every Faculty of Architecture, through hosting its projects within its city, intrinsically showcases a museum of possibilities, a testing laboratory of visions, confronting discourses, aesthetic directions, meanings and attitudes towards the existent, formulating the grounds for its particular architectural and urban hermeneutics. In a world divided to the extent of ideological fractures today, working on the project of a coherent, empowering and relevant city renders the Faculty of Architecture as a platform for building trust and collaboration.